Delays in starting morning operating lists: an analysis of more than 20000 cases in 22 German hospitals - Schuster, Martin (Deutsches Ärzteblatt, 2013)
Introduction: Delays in the start of the first operation of the day often lead to conflicts among the involved physicians and nurses. Data on such delays have already been published for individual hospitals, but robust comparative data from a large number of institutions have not been available till now. Methods: The study is based on the operating room (OR) documentation of four surgical services (general surgery, trauma/orthopedic surgery, gynecology, and ear nose throat [ENT] surgery) in 22 German hospitals over a nine-month period. Three process points (“patient arrival in OR suite,” “anesthesia ready,” and “incision”) were analyzed for the first operation of the day in each OR. Results: 21 357 operations in the first position were analyzed. The percentage of delays differed markedly for the three process points. The incision was delayed in more than 70% of the general surgical and trauma/orthopedic cases, but less often in gynecological (61 ± 24%) and ENT cases (42 ± 29%). The frequency of delays longer than 10 minutes was between 20% and 40%. The mean delay in delayed cases ranged from 14.1 ± 5.4 to 21.6 ± 8.2 minutes depending on the type of service and process point. Conclusion: The processes for the first operation of the day are not optimally structured in the hospitals whose cases were analyzed in this study. Delayed starts were common.
Gesehen am 02.08.2021